In situ histopathological and immunohistochemical characterization of rabies in the brains of naturally infected equines and bovines - Achkar, Samira Maria; Fernandes, Elaine Raniero; Guedes, Fernanda; Mori, Enio; Macedo, Carla Isabel; Duarte, Maria Irma e Seixas (Brazilian Journal of Veterinary Medicine, 2019)
The present study sought to characterize the phenomena involved in the histopathology of rabies and to assess the presence and amount of viral antigen in situ in different brain regions of naturally infected equines and bovines. The histopathological examination showed several changes due to inflammation, being most often infected cells neurons. The neuronal degeneration involved 100% of cases, in addition to a diffuse lymphocytic Infiltration and gliosis, characterized by vasculitis and perivasculitis. The presence of Negri bodies was in most cases in discreet, and the fragments with higher concentrations of antigen by both techniques employed were the cerebellum and the brain stem. Immunohistochemistry test (IHC) demonstrated greater sensitivity when applied to samples of bovines. Our results showed that in 37.5% of the total number of fragments analyzed, viral inclusions were not observed, however, there was an inflammatory process. In relation to the species, the fragments from bovine’s animals showed a slight increase when examined under this feature. These findings highlight the importance of submitting samples from suspected animals for laboratory diagnostic, even when there are no apparent abnormal histological findings.